2017
DOI: 10.1127/njgpa/2017/0648
|View full text |Cite
|
Sign up to set email alerts
|

Litholepas klausreschi gen. et sp. nov., a new neolepadine barnacle (Cirripedia, Thoracica) on a sponge from the Upper Jurassic lithographic limestones of southern Germany

Abstract: In this study we describe a unique fossil comprising 13 intact specimens of a pedunculate cirripede attached to a sponge (Codites serpentinus). The fossil comes from the Upper Jurassic lithographic limestones of southern Germany. Based on the shape and distinctive sculpture of the plates, a new genus and species Litholepas klausreschi gen. et sp. nov. (Eolepadidae: Neolepadinae) is introduced. Although lateral plates are indistinct and the rostrum is unknown, plate disposition and strong external sculpture ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…(Gili & Coma, 1998). Barnacles as epibionts can take advantage of such slowed water currents caused by sponges (Nagler et al, 2017). All the above statements might explain the reason why in this study the majority of barnacles found were arranged in groups near the surface of the host sponge.…”
Section: Discussionmentioning
confidence: 64%
“…(Gili & Coma, 1998). Barnacles as epibionts can take advantage of such slowed water currents caused by sponges (Nagler et al, 2017). All the above statements might explain the reason why in this study the majority of barnacles found were arranged in groups near the surface of the host sponge.…”
Section: Discussionmentioning
confidence: 64%
“…The third and biggest specimen GSUB V2304 lacks the posterior part of the body and the caudal fin. All specimens were collected and prepared by private collector Udo Resch (Eichstätt), who became famous for his skills in preparing fossils ( Hoffmann et al, 2020 ) and for important fossil finds of crustaceans and insects from the Upper Jurassic Solnhofen limestone in southern Germany that were exclusively collected by him and named after him and his parents ( Schweigert, 2010 ; Winkler, 2017 ; Nagler et al, 2017 ; Bechly, 2019 ). The material for this paper is deposited in the Geosciences Collection of the University of Bremen, Germany (GSUB).…”
Section: Methodsmentioning
confidence: 99%
“…The first more direct fossil indications of rhizocephalans are feminized male crabs from the Miocene (4-23 mya; Feldmann, 1998). Also important to mention in this aspect: fossils of cirripedes are well known to occur in the lithographic limestones of southern Germany (Barthel et al, 1990;Nagler et al, 2017).…”
Section: Early Fossil Record Of Cirripediamentioning
confidence: 99%